ID 45 – Central and autonomic activity during emotion processing: A multi-method approach with hemodynamic (fNIRS), electrocortical (EEG) and autonomic measures - Vanutelli, M.E.; Grippa, E.; Balconi, M. (Clinical neurophysiology, 2016)
Because of its sudden temporal evolution and representation among different levels and complex neural networks, emotion processing should be examined by means of a multi-method approach. The possibility to acquire autonomic (arousal-related) and central (cortical-related) activities allows to better elucidate the reciprocal interplay of the two compartments. 20 subjects were submitted to emotional stimuli while functional near-infrared spectroscopy (fNIRS), frequency bands (EEG) and skin conductance response (SCR) were simultaneously recorded as biological markers of emotions. Subjective measures were also considered (Self-Assessment Manikin; SAM). As shown by oxyhemoglobin (O2Hb) increasing within the right hemisphere, the contribution of the prefrontal cortex was elucidated, by pointing out a right-lateralized effect induced by the negative valence of the stimuli. Moreover EEG activity was associated with the cortical hemodynamic responsiveness to negative emotional patterns, within the right side. SCR increased in response to negative patterns and was related to explicit (SAM) and cortical (fNIRS; EEG) measures. Cortical, autonomic and subjective measures were intrinsically associated. Specifically, negative valence was more relevant to process emotional cue in relation to the hemispheric lateralization. Results suggest the importance of central and peripheral measures to explore subjects’ response to emotions.